Seasonal variation in size structure and production of autotrophic plankton community in eutrophied, low-light environment: A focus on Mesodinium rubrum - Atis Labucis; Astra Labuce; Iveta Jurgensone; Ieva Barda; Ingrida Andersone; Anda Ikauniece (Oceanologia, 2023)
Temporal variations in the primary production of the size-fractionated autotrophic plankton community were studied in coastal-estuarine waters of the eutrophic Gulf of Riga, Baltic Sea. The community was net-autotrophic during spring and summer and net-heterotrophic during autumn. The results of the present study clearly demonstrate strong covariation between net primary production (NPP) and <56 µm fractionated community biomass, particularly small-sized (16–33 µm) Mesodinium rubrum, implying that the majority of NPP stems from the lower end of the size spectrum. A pronounced size distribution shift was observed within the M. rubrum population. Large-sized (length ≥34 µm) M. rubrum was the most abundant in the first half of the productive season (until week 24), whereas small-sized M. rubrum dominated during the stratified period.